Evergreen, Montane Forests of the Western Ghats of Hassan District, Mysore State - a Contribution to the Ecology, Plant Geography and Silviculture of the Western Ghat Forests of Mysore - Kadambi, Krishnaswamy (Indian Forester, 1950)
This paper deals with one of the most exhaustive ecological cum floristic cum silvicultural studies undertaken on the evergreen mountain forests of the western Ghats in Mysore state or probably even beyond it. It has brought out the reaction upon one another of the various components forming the ecological complex of factor reigning in the of the tropical zone in general and of the evergreen forest in particular, and brings out elearly how these factors control and decide within the forest the kind, distribution, quality and climax form of the associations of trees, shrubs, herbs or other minor forms of the vegetable kingdom, be they phanerogams or other lower ones, and how the stature and distribution of each and every individual can be accounted for logically by a close study of the inter-action of the ecological factors from spot to spot. The evergreen forest, though apparently more uniform in its constitution than the other kinds, is actually more diversified in its form and composition than any which nature has produced in the tropies : there is probably no place on earth where plants are so closely situated physically, yet so diversified or separated or rendered complex in their ecological bearing and structure as in this evergreen forest: and there is probably no forest on earth which excels the moist, tropical, mountainous evergreen in its accumulation of the natural habitats both in their number and variety.